Optimized space-vector modulation to reduce neutral point current for extending capacitor lifetime in three-level inverters - An, Sang Won; Kim, Seok Min; Lee, Kyo Beum (IEEE Access, 2020)
In this paper, an optimized space-vector modulation (SVM) to reduce DC-link ripple current in three-level inverters is presented. Various types of capacitors can be utilized to balance the voltage in the DC-link of voltage source inverters. Electrolytic capacitors are widely used owing to their large capacitance per volume. However, electrolytic capacitors have a short lifespan because the allowable ripple current is low. A conventional SVM that is focused on improving harmonic characteristics. Therefore, it cannot balance the DC-link ripple current properly because using some voltage vectors increases the DC-link ripple current. To overcome this limitation and extend the lifespan of the capacitors, an optimized SVM is proposed to reduce the DC-link ripple current. The proposed modulation scheme synthesizes the reference voltage by choosing voltage vectors that cause smaller increases in the DC-link ripple current, avoiding those that cause larger increases. The effectiveness of the proposed optimized SVM is verified by simulations and experimental results.
Keywords: Harmonic characteristics; Modulation schemes; Reference voltages; Ripple currents; Space Vector Modulation; Space vector modulations (SVM); Three-level inverters; Voltage source inverter; capacitor; dc-link ripple current; reliability; space-vector modulation; Three-level inverter